Development of Incentive Model for Photovoltaic Generators to Participate in a Day-ahead Electricity Market in South Korea - Kong, Junhyuk; Jung, Jaesung (2019 IEEE PES Innovative Smart Grid Technologies Asia, ISGT 2019, 2019)
This paper presents the incentive model when Photovoltaic (PV) generator participates in a day-ahead market in South Korea. For this, the current supporting policy for PV generation and rules of a day-ahead market are analyzed. Because of the lack of the incentive model for PV supplier in a day-ahead market, Independent System Operation (ISO) can't consider PV generation when they plan the short-term supply of the system. Therefore, the proposed incentive model is developed to provide the additional profit to encourage PV supplier to participate in the market based on the accuracy of PV generation bidding. To verify incentive model, the actual data including PV generation, System Marginal Price (SMP) and Renewable Energy Certificate (REC) price are used.
Keywords: Day-ahead electricity market; Energy storage systems; Incentive models; Independent systems; Photovoltaic; Renewable energy certificates; Supporting policies; System marginal price; Day-ahead Electricity Market; Energy Storage System (ESS); Incentive Model; Photovoltaic (PV)